Organic and mineral fertilizer effects on the yield and mineral contents of carrot (Daucus carota) - Kovács, A. B.; Kremper, R.; Jakab, A.; Szabó, A. (International Journal of Horticultural Science, 2012)
A greenhouse pot experiment was conducted to investigate the effects of ammonium-nitrate, food waste compost, bacterial fertilizer (EM-1) and their combinations on production and nutrient contents of carrot. The study was conducted on a calcareous chernozem and acidic sandy soils in a randomized complete block design with 8 treatments and four replications. NH4NO3 in chernozem soil increased the weight of carrot leaves only, while in sandy soil resulted in reduced yield and highly increased NO3-N content of roots. Sandy soil showed higher response of biomass production to food waste compost application than chernozem soil. The highest carotenoid content of roots was measured with compost treatment. Combined application of compost and NH4NO3 in chernozem proved to be good combination but in sandy soil have turn out to be less favourable than sole compost treatment. Bacterial fertilizer (EM-1) did not cause marked effect on the yield parameters, but caused increased phosphorus content of plant. In chernozem soil the maximum yield parameters were achieved with the combined treatment of ammonium-nitrate+compost+EM-1. In sandy soil the most favourable treatment proved to be the compost treatment. Results suggest that application of food waste compost as a nutrient source could be a promising agrochemical practice especially in soils having low organic material and low nutrient supply.